Bon Jovi live at Madison Square Garden [videorecording (DVD)] - Bongiovi, Anthony; Lockwood, Brian, 1959- (Island Def Jam Music Group, 2009)
Nineteen years to the day after Bon Jovi first performed there, they returned to the same stage for the last date of their historic Lost Highway tour, officially the biggest tour on the planet in 2008.